Factors Related To Compliance With Paying Monthly Bpjs Kesehatan Mandiri Participants Contributions In The Informal Sector In Jambi City - Yani, Helma Vira; Dwi Noerjoedianto; Andy Amir; Adila Solida; Arnild Augina Mekarisce (Jurnal EduHealth, 2023)
Compliance with independent participants in paying National Health Insurance (JKN) contributions in Jambi City is not optimal. This is because Jambi City is the district/city that has the largest number of independent participants in arrears, namely 103,195 (16.95%) participants. Contributions greatly influence the smooth running of BPJS Health so that there is no deficit. The aim of this research is to determine the factors associated with compliance with paying monthly BPJS health contributions for independent participants in the informal sector in Jambi City. This research uses a cross sectional design, with purposive sampling data collection techniques. The samples taken were 139,091 independent BPJS participants in the informal sector. Analysis was carried out using univariate and bivariate tests with the chi-square test. The results of the study show that there is a relationship between education (p-value=0.039) and income (p-value=0.005) with compliance with paying BPJS Health contributions and there is no relationship between employment (p-value=0.190), contribution rates (p-value =0.129) and access to payments (p-value=0.887) with compliance in paying BPJS Health contributions for independent participants in the informal sector in Jambi City. BPJS Health must strictly enforce sanctions in accordance with applicable regulations if payments are late. People are expected to choose a treatment class that suits their ability to pay JKN contributions or if they feel they cannot afford it, people can apply to become PBI participants.